Identification of a novel recombinant polerovirus and other emergent viruses and tombusvirus-like associated RNA species associated with carrot motley dwarf disease in the United States - Erickson, Anna; Ter Horst, Anneliek M.; Carlson, Curtis R.; Falk, Bryce W.; Kuo, Yen-Wen (Frontiers in Microbiology, 2024)
In 2020 and 2021 carrot samples from Washington, United States (U.S.), and parsley and cilantro samples from California, U.S., exhibiting typical symptoms of carrot motley dwarf (CMD) disease were submitted to our lab for diagnosis. While initial RT-PCR diagnostic assays identified the typical CMD viruses—the polerovirus carrot red leaf virus, the umbraviruses carrot mottle virus and/or carrot mottle mimic virus, and tombusvirus-like associated RNAs (tlaRNAs)—in the Washington carrot samples, only umbraviruses and tlaRNAs were detected in the parsley and cilantro samples. Since umbraviruses and tlaRNAs rely on co-infection with a helper polerovirus to gain aphid transmissibility, we retested these samples with another RT-PCR assay for generic polerovirus detection. Unexpectedly, the poleroviruses Torilis crimson leaf virus (TorCLV) and fennel motley virus were identified in these samples. Subsequent RNA sequencing analysis was conducted to confirm these results and look for other emergent viruses. In addition to confirming the initial diagnostic results, the recently described polerovirus Foeniculum vulgare polerovirus, umbraviruses Pastinaca umbravirus 1 (PasUV1) and wild carrot mottle virus (WCMoV), and tlaRNA Arracacha latent virus E associated RNA (ALVEaRNA) were identified, making this the first report of these viruses and tlaRNA in the U.S. Of particular interest, we also identified a putative novel polerovirus that appears to be a recombinant between carrot polerovirus 1 (CaPV1), sharing 92% amino acid identity with the RNA dependent RNA polymerase in the 5’ gene block of this virus, and TorCLV, sharing >98% amino acid identity with the capsid protein in the 3’ gene block. This work adds to the growing list of polerovirus species exhibiting recombination between the 5’ and 3’ gene blocks, and highlights the unique, variable, and dynamic associations that can occur in polerovirus, umbravirus, and tlaRNA disease complexes.